2023
DOI: 10.1590/1980531410136
|View full text |Cite
|
Sign up to set email alerts
|

Comunidades De Aprendizagem: Efeitos E Desafios - Uma Scoping Review

Generosa Pinheiro,
José Joaquim Matias Alves

Abstract: Resumo O objetivo central desta scoping review, realizada segundo o quadro metodológico de Arksey e O’Malley, é compreender as mudanças organizacionais, culturais e pedagógicas geradas pelas Comunidades Profissionais de Aprendizagem, em meio escolar, nos últimos cinco anos, e encontrar, na literatura revista, lacunas que possam informar futuras investigações. Os resultados indicam que, embora os estudos sobre essas comunidades sejam numerosos e revelem os seus efeitos positivos, eles estão, essencialmente, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…In an exploratory literature review on the cultural changes generated by PLCs at schools, Pinheiro and Alves [9], like Stoll et al [5], found positive results regarding the effects of PLCs on organizational culture, more specifically in promoting a culture of collaboration and collegiality and, consequently, in developing teachers' professionalism [20][21][22][23][24].…”
Section: Learning Communities and Organizational Culturementioning
confidence: 98%
See 1 more Smart Citation
“…In an exploratory literature review on the cultural changes generated by PLCs at schools, Pinheiro and Alves [9], like Stoll et al [5], found positive results regarding the effects of PLCs on organizational culture, more specifically in promoting a culture of collaboration and collegiality and, consequently, in developing teachers' professionalism [20][21][22][23][24].…”
Section: Learning Communities and Organizational Culturementioning
confidence: 98%
“…However, there is little consistent evidence on how participation in PLCs promotes changes in teaching practice [8] or the transformation of a school into a learning organization [9]. It should also be noted that PLCs and collaboration alone do not lead to learning for students, teachers or organizations [5].…”
Section: Introductionmentioning
confidence: 99%